Spiritual relationship, resilience and coping strategies on readiness of seeking guidance and counselling services among substance abuse secondary students - Abdul Basar, Siti Fatimah; Zainudin, Zaida Nor; Wan Othman, Wan Norhayati; Engku Kamarudin, Engku Mardiah; Sumari, Melati; Abdul Ghafar, Nurul Nadia; Mohamad Yusop, Yusni (Human Resource Management Academic Research Society, 2022)
This study aimed to analyse the spiritual relationship, resilience, and coping strategies on readiness to seek Guidance and Counselling services for substance abuse among secondary students. The 136 respondents who participated in this study consisted of Form 1, 2, and 4 students who were involved in substance abuse. The Pearson correlation analysis was used to determine the relationship between spiritual, resilience, and coping strategies in seeking Guidance and Counselling services. Results of the study showed the relationship between spirituality and resilience with seeking Guidance and Counselling services had a very weak positive correlation. The relationship between coping strategies and seeking Guidance and Counselling services found that engagement coping strategies have a moderately strong positive correlation and withdrawal coping strategies have very weak positive correlations. These findings are very important for counsellors to improve in establishing more effective services or methods of intervention against substance abuse students in the future.